2009
DOI: 10.1002/rra.1266
|View full text |Cite
|
Sign up to set email alerts
|

Microinvertebrate dynamics in riverine slackwater and mid‐channel habitats in relation to physico‐chemical parameters and food availability

Abstract: Microinvertebrates play a critical role in riverine food webs, and recent studies have hypothesized that slackwaters, non-flowing regions associated with the main channel, are important for their reproduction and recruitment. However, little is known regarding the population and community dynamics of microinvertebrate communities in slackwater regions, or how they compare with those in mid-channel regions. This study examined microinvertebrate communities in the epibenthic and pelagic zones of slackwater and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 47 publications
(85 reference statements)
2
20
0
1
Order By: Relevance
“…Hydraulic criteria are commonly species specific and life stage dependent [Hancock and Bunn, 1999;Schiemer et al, 2001]; however, low velocities are clearly an important consideration with respect to mechanisms such as swimming ability of fishes [Koehn et al, 1994;Bowen et al, 1998;Price, 2007] and hydraulic residence time for invertebrates [Schiemer et al, 2001; King and Crook, 2002] and phytoplankton [Hein et al, 2004]. Mechanistic relationships cannot be discounted when supported by overwhelming empirical evidence [Ning et al, 2010].…”
Section: Ecologically Derived Hydraulic Characterization Of Slackwatersmentioning
confidence: 99%
See 4 more Smart Citations
“…Hydraulic criteria are commonly species specific and life stage dependent [Hancock and Bunn, 1999;Schiemer et al, 2001]; however, low velocities are clearly an important consideration with respect to mechanisms such as swimming ability of fishes [Koehn et al, 1994;Bowen et al, 1998;Price, 2007] and hydraulic residence time for invertebrates [Schiemer et al, 2001; King and Crook, 2002] and phytoplankton [Hein et al, 2004]. Mechanistic relationships cannot be discounted when supported by overwhelming empirical evidence [Ning et al, 2010].…”
Section: Ecologically Derived Hydraulic Characterization Of Slackwatersmentioning
confidence: 99%
“…[3] Slackwaters have been found to contain significantly greater numbers of fish, shrimp, and zooplankton than midchannel habitats in lowland rivers [Bowen et al, 2003;Richardson et al, 2004;Nielsen and Watson, 2008;Ning et al, 2010] with an order of magnitude more fish and shrimp observed in one study [Humphries et al, 2006]. They have also been found to provide refuge from excessively high-water velocities, which stress many biota [Schiemer et al, 2001;Maddock et al, 2004] enabling recolonization of the channel following flow recession [Lancaster and Belyea, 1997;Speirs and Gurney, 2001].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations